Effect of hybridization in CoDico-FRTPs: Orientation-dependent characterization and analytical modeling in various climatic conditions - Marian Scheuring, Benedikt (KIT Scientific Publishing, 2026)
Long fiber-reinforced thermoplastics (LFT) offer great potential for lightweight construction in large-scale automotive production. This study examines LFT-D-ILC with a PA6 matrix and various fibers, as well as hybrid materials made from CF-LFT and unidirectional tapes, in terms of their directional properties under tensile and bending loads. Hybridization improves stiffness and environmental resistance without losing the advantages of LFTs, such as short cycle times.